Utilisation of Agriculture Waste in Concrete to Enhance Its Properties - Pathak, Niket; Garg, Deepak; Singh, Aditya (International Journal of Scientific Research in Civil Engineering, 2024)
Concrete is the most extensively used man-made construction material in the world. Its most important quality is its versatility and the ability to design the concrete of any required properties according to the environment. Human development in today’s scenario is impossible without the excessive use of concrete. Cement is the most important component of concrete. Unfortunately production of cement emits a very large amount of greenhouse gases and possess a very potential threat to the atmosphere. Thus it is inevitable for the sustainable development of human life that the dependency on cement to obtain strength in concrete should be lowered. This is the main reason to obtain a suitable replacement of cement to obtain high strength concrete at a low cost incurred. Also the modern constructions require very high strength in concrete which is only possible by mixing a suitable quantity of admixtures in the concrete. The earth is abundant with two types of agricultural waste and sawdust. However, disposing of such large amounts of agricultural waste has become a major environmental threat. Research has shown that the byproducts of both materials have pozzolanic properties that allow them to be partially substituted for cement in the construction industry, creating environmentally friendly concrete and reducing the emission of harmful gases that are produced when cement reacts during concrete formation. Their disposal has gotten more expensive as a result of the most recent laws and regulations. Therefore, it’s imperative to identify a suitable and beneficial application for these waste materials. Due to their high siliceous content and pozzolanic qualities, these materials can be added to concrete mixes as an additive to achieve high strength or utilized in place of cement. The two main factors that affect how well concrete performs in any field application are its flexural and compressive strengths. It is therefore important to find out how these admixtures affect the concrete’s compressive and flexural strengths. One way to determine which admixture is best for a given case is to conduct a comparison research that evaluates the relative effects of these admixtures on concrete strength.